The Academic's Handbook, Fourth Edition : Revised and Expanded - Olcott, Jocelyn, 1970-; Flores, Lori A. (Book collections on Project MUSE., 2020)
"This Fourth Edition of The Academic's Handbook provides helpful advice to academics at every career stage, from entering the job market through settling into a first job to the tenure process and then onto navigating leadership and administrative roles. The last edition of the Handbook was published in 2007. This new edition has been revised and updated to reflect important changes and trends in academia over the last decade. Contributors reflect the diversity of scholars in the academy and essays acknowledge and address the fact that there is no longer a "conventional" or "typical" academic or academic position. This edition tackles topics such as the increasing "adjunctification" of the academy; the debates around technology, social media, and free speech in classrooms and wider campus communities; successful publishing and grant-writing strategies in a changing landscape of resources; and the rising number of mental illness diagnoses among students, staff, and faculty"--